Thickness effects on the critical crack tip opening angle fracture criterion in 2024-T351 aluminum - Mahmoud, Samer Hassan (Kansas State University, 2000)
The critical crack tip opening angle (CTOA) is a promising fracture criterion for characterizing stable crack growth. However, material thickness effects on the critical CTOA have not been fully characterized. The goals of this investigation were to experimentally and computationally evaluate the effect of material thickness on the characterization of the CTOA parameter. Fracture tests were conducted on 8 in. wide compact tension fracture specimens machined from 2024-T351 Aluminum alloy. This material was selected in order to allow for the direct comparison to, and extension of, previously evaluated thin -sheet form of the 2024-T3 alloy. The range of thickness chosen for this research included 0.090, 0.25, 0.5, and 1.0 inch. The experimental set-up allowed for real-time monitoring of the crack tip, acquisition of still -images, and the continuous recording of the entire stable tearing process. During the fracture tests, the load and load line displacement signals were continuously recorded. After test completion, the entire image history was reviewed to obtain CTOA and crack length measurements using the optical microscopy and digital image correlation methods. Both three- and two-dimensional elastic -plastic finite element fracture analyses were then used to simulate the stable tearing tests. The experimentally measured CTOA (on the surface of the specimens) decreased with increasing specimen thickness and appeared to be asymptotically reaching a lower limiting value. As reported in earlier studies on thin -sheet 2024-T3 alloy, the experimentally determined CTOA became nearly constant after a small amount of crack extension and remained constant over a wide range in thickness. In addition, the nonconstant CTOA region and the scatter in measured CTOA values became smaller for the thicker specimens. Three-dimensional computationally generated CTOA values (at the specimen center) were higher than the experimentally determined surface CTOA values for the three largest thicknesses. Using the CTOA values from the three-dimensional analyses, two-dimensional fracture analyses were performed to obtain the plain strain core height. Based on these analyses, the plain strain core height was seen to increase with increasing specimen thickness. Both of the two-dimensional and three-dimensional finite element based analyses produced good approximations of the measured crack extensions and load line displacements.